2014
DOI: 10.1371/journal.pone.0092829
|View full text |Cite|
|
Sign up to set email alerts
|

Validity of Electronically Administered Recent Physical Activity Questionnaire (RPAQ) in Ten European Countries

Abstract: ObjectiveTo examine the validity of the Recent Physical Activity Questionnaire (RPAQ) which assesses physical activity (PA) in 4 domains (leisure, work, commuting, home) during past month.Methods580 men and 1343 women from 10 European countries attended 2 visits at which PA energy expenditure (PAEE), time at moderate-to-vigorous PA (MVPA) and sedentary time were measured using individually-calibrated combined heart-rate and movement sensing. At the second visit, RPAQ was administered electronically. Validity w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
83
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(88 citation statements)
references
References 51 publications
1
83
0
Order By: Relevance
“…The four sets of starting data from Method A were: (1) duration (minutes per day) of moderate to vigorous physical activity (MVPA) derived from the Recent Physical Activity Questionnaire (RPAQ) (Besson, Brage, Jakes, Ekelund, & Wareham, 2010); (2) total daily PAEE expressed in kJ•day -1 •kg -1 derived from RPAQ; (3) the four-level categorical Cambridge Index derived by combining occupational physical activity with time participating in cycling and other physical exercise, giving categories of inactive, moderately inactive, moderately active, and active (Golubic et al, 2014;Peters et al, 2012;Wareham et al, 2003); and (4) the mean daily high-pass filter vector magnitude signal from non-dominant wrist acceleration expressed in milli-g (ACC WRIST ) (White et al, 2018;White, Westgate, Wareham, & Brage, 2016).…”
Section: Specific Harmonisation Taskmentioning
confidence: 99%
See 1 more Smart Citation
“…The four sets of starting data from Method A were: (1) duration (minutes per day) of moderate to vigorous physical activity (MVPA) derived from the Recent Physical Activity Questionnaire (RPAQ) (Besson, Brage, Jakes, Ekelund, & Wareham, 2010); (2) total daily PAEE expressed in kJ•day -1 •kg -1 derived from RPAQ; (3) the four-level categorical Cambridge Index derived by combining occupational physical activity with time participating in cycling and other physical exercise, giving categories of inactive, moderately inactive, moderately active, and active (Golubic et al, 2014;Peters et al, 2012;Wareham et al, 2003); and (4) the mean daily high-pass filter vector magnitude signal from non-dominant wrist acceleration expressed in milli-g (ACC WRIST ) (White et al, 2018;White, Westgate, Wareham, & Brage, 2016).…”
Section: Specific Harmonisation Taskmentioning
confidence: 99%
“…METs (Ainsworth et al, 2011), estimates of PAEE calculated as frequency * duration * intensity (Besson et al, 2010), and the four-level Cambridge Index (Golubic et al, 2014;Wareham et al, 2003). The ACC TRUNK signal from the combined heart and movement sensor was used in the format of mean daily trunk acceleration in m•s -2 , while the HR signal together with treadmill test data was used to derive an individually calibrated estimate of PAEE as previously described (Brage et al, 2007(Brage et al, , 2015.…”
Section: Bridge Equation Ac Five Variations On Bridge Equation Ac Wementioning
confidence: 99%
“…The physical activity and sedentariness of the subject was collected by validated questionnaires: -for subjects aged 18-79 years old: the Recent Physical Activity Questionnaire (RPAQ) was included in the SA questionnaire (Golubic, May et al 2014 The present document has been produced and adopted by the bodies identified above as authors. This task has been carried out exclusively by the authors in the context of a contract between the European Food Safety Authority and the authors, awarded following a tender procedure.…”
Section: Physical Activitymentioning
confidence: 99%
“…The physical activity and sedentariness of the subject was collected by validated questionnaires: -for subjects aged 18-79 years old: the Recent Physical Activity Questionnaire (RPAQ) was included in the SA questionnaire (Golubic, May et al 2014); -for children aged 11-17 years old: the validated Youth Risk Behaviour Survey (YRBS) questionnaire was included in the FF questionnaire (Troped, Wiecha et al 2007); -for children aged 3-10 years old: a French-specific questionnaire, developed and compared with an accelerometer in children aged 6-10 years old, was included in the FF questionnaire. The present document has been produced and adopted by the bodies identified above as authors.…”
Section: Physical Activitymentioning
confidence: 99%
“…Diet-induced thermogenesis is less variable and ordinarily constitutes approximately 10% of total energy expenditure 4 . The predominant source of uncertainty in total energy expenditure estimates is the highly-variable activity energy expenditure component, which has proven difficult to capture by subjective instruments such as questionnaires 5,6 . Body-worn sensors such as accelerometers have the potential to provide a relatively cheap and reliable solution to this problem 7 , if valid inference models can be devised to estimate activity energy expenditure from the measurements they record.…”
Section: Introductionmentioning
confidence: 99%